Antioxidant and antiproliferative activity of indigocarpan, a pterocarpan from Indigofera aspalathoides. (27th July 2016) - Mahajan, Pravin; Gnana Oli, Rajaraman; Jachak, Sanjay M.; Bharate, Sandip B.; Chaudhuri, Bhabatosh
Abstract: Objectives: This study aimed to investigate the anticancer potential of indigocarpan (1 ), a pterocarpan isolated from Indigofera aspalathoides, a plant found in India which has been used in Ayurveda for centuries for the treatment of oedematous tumours. Methods: The antiproliferative activity in a panel of four human cancer cell lines was studied. The mechanism of its antiproliferative activity in human colorectal adenocarcinoma LS174T cells was investigated in detail. Key findings: Indigocarpan (1 ) showed antiproliferative activity in a panel of four human cancer cell lines with IC50 s ranging from 180 to 250 μm . Indigocarpan induces p53‐dependent p21 upregulation and apoptosis in LS174T cells, upregulates p53 and p21 WAF1 protein levels, enhances cleavage of caspase‐3 and downregulates cyclin D1, cyclin B1 and PCNA protein levels, indicating its role in modulating cell cycle progression. Indigocarpan also exhibited a strong antioxidative effect in LS174T cells. Conclusions: Along with the antiproliferative capacity, the strong antioxidative property of the compound makes it a promising candidate for further development as an anticancer and chemopreventive compound.